Town without pity [videorecording (DVD)] - Reinhardt, Gottfried; Douglas, Kirk, 1916-2020-; Marshall, E. G., 1914-1998; Blake, Robert, 1933-; Jaeckel, Richard, 1926-1997; Gregor, Manfred, 1929- (MGM Home Entertainment, 2002)
Four American GI's, stationed in Germany circa 1960, are accused of attacking a local teenage girl. An Army major is assigned to defend the soldiers. If he's going to prevent their death sentences, he will have to turn the spotlight on the victim who is already traumatized.